Legami e origini - Debora Mantovani (Quaderni di Sociologia, 2015)
Foreign youngsters experiencing migration are often described as mantaining a precarious balance, insofar as they develop a sense of belonging to their host societies and, at the same time, maintain a strong tie with their countries of origin. This paper aims to investigate foreign youths’ integration within the host society, with particular emphasis on their sense of belonging to a specific place and the construction of their identity. A comparison with Italian youths’ identity has been investigated as well, since even today many students have experienced domestic migration, which may influence their sense of belonging. In order to explore this topic, data collected in a survey conducted in the province of Bologna in the school year 2006/07 are examined. More than 3,000 Italian and foreign teenagers enrolled in upper secondary schools were interviewed via a structured questionnaire. Comparison between foreigners and Italians reveals an interesting – though not unexpected – difference in terms of national identities: the former are more likely to maintain a tie with their country of origin, whereas the latter especially express a link with the Italian context. Nonetheless, this unsurprising difference partially fades if, on the one hand, foreigners born in Italy are compared to Italians and, on the other, immigrant foreigners are compared to Italians’ having experienced migration. Finally, length of stay in the host/land of origin and language/dialect spoken at home are two crucial variables linked to both Italian and foreign immigrants’ ties with the place of origin.